Mastery in coaching a complete psychological toolkit for advanced coaching - Passmore, Jonathan (Kogan Page, 2014)
"The reasons that coaching works so well and can produce such dramatic results are grounded in psychology, so it follows that some of the most powerful coaching methods available draw on psychological thinking.This up-to-the-minute guide presents the latest thinking on the most effective techniques coaches can use with their clients. Every chapter is written by a leading expert, and takes a rigorous, evidence-based approach to provide a practical understanding of each method, as well as the underpinning psychological coaching concepts. Ranging from cognitive-behavioral coaching, Gestalt and positive psychology to neuroscience and mindfulness, this book provides coaches the tools they need to get the best from their clients. "